Adsorption of Basic and Acid Dyes Using Palm Kernel Shell - Based Activated Carbon - Arsyad, Jumasiah (2005)
A series of batch laboratory studies were conducted in order to investigate the practicability of palm kernel shell (PKS)-based activated carbon for removal of basic dye, Basic Blue 9 (BB 9) and acid dye, Acid Orange 52 (A0 52) from their aqueous solutions. Three different particle sizes of PKS were used and categorized as PKS - S, PKS - M and PKS - L. The adsorption capacities of the PKS-based activated carbons were compared with those of commercial grade coal-based activated carbons at the same conditions. All batch experiments were carried out at a constant temperature of 28°C (22°C) using incubator shaker that operated at 150 rpm. Batch equilibrium study shows that Adsorption of BB 9 and A0 52 were highly pH dependent. Removal of BB 9 increased with pH with maximum removal observed at pH 7.0, and decreased thereafter with further increase in the initial pH. However, pH effect on A0 52 removal shows that A0 52 removal decreased with an increase in initial pH with the optimum initial was observed at 3.5.Batch equilibrium data also a had good agreement with the Langmuir, Freundlich and Redlich-Peterson isotherm models with correlation coefficients > 0.9. Overall, the Redlich-Peterson isotherm showed the best fit for all adsorbents under investigation in terms of correlation coefficient as well as error analysis of the results. For all the systems in this study, the analysis of isotherm shape factor showed that adsorption was favorable. For the adsorbents under investigation, PKS-S has the highest adsorption capacity followed by PKS-M. PKS-L and commercial coal based pellet form have almost equally-balanced adsorption capacity. Of all the adsorbents, commercial coal-based in powder form exhibits the lowest adsorption capacity. Obtained results revealed that PKS based activated carbon is a highly potential alternative adsorbent for treatment of dye-containing wastewater. The maximum capacity of the adsorbents for BB 9 were 333.33 mg/g, 322.58 mg/g and 212.77 mglg for PKS - S, PKS - M and PKS - L, respectively, while for powder and pellet commercial grade coal based, the capacities were 204.08 mg/g and 217.39 mg/g, respectively. On the other hand, the maximum capacities of the same adsorbents for A0 52 were 344.83 mg/g, 333.33 mglg, 263.16 mg/g, 238.09 mg/g and 322.58 mg/g, respectively. Adsorption capacities of the same adsorbents were found to be higher for adsorption of A0 52 compared to those of BB 9 due to the smaller molecular size of the former. Batch kinetic studies were also performed to investigate the rate limiting of the adsorption process. Results obtained revealed that the adsorption of both BB 9 and A0 52 was rapid at the beginning, but approached equilibrium slowly.Experimental data can be modeled using pseudo-second-order kinetic model as first order kinetic model does not represent the whole range of adsorption process. Other than that, intraparticle diffusion was found to be prominent at a certain stage of adsorption but it would not be the only limiting step that controlled the adsorption dynamic. Kinetic data also showed that the adsorption rates were a function of initial adsorbate concentration, adsorbent particle size and adsorbent mass. For all systems under consideration, the values of kZ increased significantly as adsorbent dose increases. Nevertheless, the values of k2 were inversely proportional to the initial adsorbate concentration and adsorbent particle size. On the other hand, values of k, were found to be directly proportional to the initial adsorbate concentration but decreased gradually as adsorbent particle size and adsorbent dose increases.